(untitled) (Journal of history, 2024)
In this article, the author examines hospitality in Kazakh society as a traditional institution, noting the impact of globalization and urbanization today. The research work is based on materials collected during expeditions to various regions of Kazakhstan. Based on sources and special literature related to the topic, some features of hospitality etiquette were analyzed: the distribution of guests by category, the order of their reception, the rules of behavior of hosts and visitors, the arrangement of adults at the table and the types of dishes served with meat, as well as gender roles at the reception. The author examines general and personal, traditional and new aspects of etiquette. The etymology of the term Kut and its use in combination with the concept of guest are investigated. Despite the fact that the traditions of hospitality have undergone significant changes, they still remain the most important value of modern Kazakh society. The results of the sociological survey used in the article showed the peculiarities of respect for the guest among the Kazakhs of Tarbagatai, as well as various types of gifts. Using the comparative historical method, the peculiarities of the differences between the regions of Kazakhstan and the changes taking place at the present stage are highlighted.